Comparative In silico Analysis of Enzymatic Degradation Resistance in Resin-matrix Ceramics - Özay Önöral; Ahmet Ozer Sehirli; Emine Erdag (Biomedical and Biotechnology Research Journal)
Background: Resin-matrix ceramics (RMCs) are commonly used in prosthetic dentistry due to their ability to closely replicate the optical and mechanical characteristics of natural teeth. However, their long-term performance can be compromised by biodegradation, especially through exposure to esterases. This study aimed to evaluate the resistance of RMCs to enzymatic degradation by analyzing the interaction of their organic components with four key esterases. Methods: A computational approach combining molecular docking and molecular dynamics simulations was employed to assess the biodegradation resistance of RMCs. Organic components of RMCs were simulated and docked with these enzymes. Binding affinities (ΔGbind values) were calculated to evaluate the interaction strength. Molecular dynamics simulations were conducted for 100 ns to assess the structural stability of the organic components. Statistical analyses were performed, including one-way analysis of variance and Tukey’s post hoc test (α =0.05), to identify significant differences among the tested materials. Results: Among the materials tested, RMC1 had the lowest negative ΔGbind values, indicating the strongest resistance to enzymatic degradation. Molecular dynamics results further highlighted the structural stability of these components, contributing to their enhanced resistance. Conclusions: The findings suggest that the chemical composition plays a key role in resistance to enzymatic breakdown. Further in vitro studies are recommended to validate the preliminary findings of this study and explore strategies to enhance the durability of RMCs in clinical settings.